The Implementation of Virtual Reality (VR) of Laboratories for Campus Marketing and Promotion - Luqman Umar; Hendra Jatnika; Mochamad Farid Rifai; Karina Djunaidi; Yasni Djamain; Yudhi S. Purwanto; Afief Fadlan Yudri; Indah Wulandari; Andi Dahroni (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
ITPLN's promotional target range extends to the entirety of Indonesia. At present, campus admissions only focus on 35 out of the 38 provinces, with a limited number of students from the remote and outlying areas. Several promotional techniques have been implemented, yielding satisfactory results; however, there is room for improvement. To enhance its efforts, ITPLN utilizes VR technology to showcase campus facilities through virtual media. The Virtual Reality laboratory at ITPLN offers virtual tours that introduce various laboratories in all faculties. These tours serve two important purposes: supporting lectures in the laboratory and promoting the campus. The integration of laboratory introductions as a promotional tool is deemed appropriate for several reasons, including wider coverage, more comprehensive information, and an immersive and interactive experience. Consequently, prospective ITPLN students no longer need to physically visit the campus to gain a comprehensive understanding of the laboratory and campus in general. The development of VR facilities followed the Multimedia Development Life Cycle (MDLC) method, and thorough testing was conducted to refine the existing VR resources. The outcome of this process is nine laboratory tours that highlight VR-based practical and research facilities, which can further enhance web-based learning and campus promotion.